HEALTHY EATING PATTERNS AND PHYSICAL ACTIVITY STATUS OF ADOLESCENTS - (:unkn) unknown (NOBEL ILAC, 2012)
Objective: To determine physical activity status and knowledge, attitude and behavior of adolescents regarding healthy eating. Material and Method: 375 students, from the first year of a state high school in Uskudar, Istanbul, were enrolled in this descriptive study. Participants were filled in a questionnaire including 21 questions about nourishment and physical activity. Participants were considered as knowledgeable if they write 3 food groups in food pyramid in correct consuming order and as eating healthy if they declared to consume at least three food groups in correct order Results: Mean age of the participants was 15.34 +/- 0.63 and 54.4%were female. Among the participants, 50.1% have breakfast every day, %63.9 ships at least one meal a day, and 49.7%participates a sport activity regularly. %39.3 knows food pyramid and %23.3 eat healthy Girls eat significantly more healthier than boys and boys are more sportive than girls (p<0.05). Conclusion: Knowledge about food pyramid of our participants was not adequate and they were not eating healthy. There is a need to implement educational healthy eating programs targeting adolescent age group.
Keywords: Adolescent health; food pyramid; gender; nutritional habits; exercise and nutrition; DIETARY-INTAKE; FOOD-INTAKE; ASSOCIATIONS; ENVIRONMENT; VEGETABLES; OBESITY; PARENT; CHILD